Pengaruh Kombinasi Mocaf dan Tepung Tempe Sebagai Bahan Pengisi Terhadap Karakteristik Snack Bar Anggur Laut dan Edamame - Amalia Wahyuningtyas; Zada Agna Talitha; Retno Dwi Lestari (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2026)
Snack bars are processed food products characterized by a solid, bar-shaped form, typically made from ingredients such as wheat flour, cereals, dried fruits, nuts, and other food ingredients that are combined using a binding agent. Snack bars have the potential to serve as a snack to prevent stunting due to their complete nutritional content. This study utilizes local food ingredients, namely high-fiber sea grapes and mineral-rich edamame as toppings. Additionally, mocaf and tempeh flour are used as fillers because they are gluten-free and serve as the primary nutritional sources for the snack bars. This study aims to determine the effect of the combination of mocaf and tempeh flour on the hardness, color, iron content, zinc content, crude fiber, and organoleptic characteristics of sea grapes and edamame snack bars. The method used in this study was a Completely Randomized Design (CRD) with five treatment combinations of mocaf and tempeh flour (100:0, 60:40, 50:50, 40:60, 0:100) with two replicates in duplicate. The research data were analyzed using ANOVA, followed by DMRT at a 5% significance level. The results showed that the combination of mocaf and tempeh flour significantly affected color characteristics (L* and a*), iron content, zinc content, crude fiber, color organoleptics, texture, taste, and overall quality, but did not significantly affect hardness, color (b*), and aroma organoleptics in sea grapes and edamame snack bars. Thus, the combination of food ingredients can be used to produce nutritious snack bars with potential to serve as a snack alternative for stunting prevention.